A bulk-driven, buffer-biased, gain-boosted amplifier for biomedical signal enhancement. Issue 1 (1st January 2019) - Mythry, Sarin Vijay; Moni, D. Jackuline
Abstract: The growing consciousness in health, biomedical research area is becoming most sought-after to develop or design medical devices by bringing biomedical researchers and clinicians to solve many health issues. Biomedical electronics is the endorsement and resolution of many techniques in engineering powered biology and medicine. The medical imaging accounts the design and development of electrophysiological monitoring devices to examine the whole human body for proper diagnosis. The biomedical signals are low amplitude, low frequency, are to be amplified in the range of millihertz to kilohertz while rejecting the dc offsets, created a tremendous demand amongst neuroscience researchers and clinicians. In this design capacitive feedback, neural signal recording amplifier is designed using folded cascode operational transconductance amplifier (OTA). The neural amplifier uses an AC coupled input signal to segregate the DC offset voltages generated at electrode-nerve interface due to chemical reaction and AC coupled input also represses the flicker noise. A large resistor, implemented using two series MOS devices as pseudo resistors, used in parallel to capacitive feedback to exploit device off-resistance for DC feedback normalization. This article presents a bulk-driven, buffer-biased, gain-boosted amplifier for biomedical signal is designed using 90 nm CMOS technology to capture signal activity. The bulk-driven folded cascode topology is used to design amplifier, which has reduced threshold voltage and supply voltage by consuming half the power of the conventional gate driven counter parts. The proposed and designed bulk-driven folded cascode operational transconductance amplifier (BD FC-OTA) achieved a gain of 81 dB, 39 nV/√ Hz is the recorded noise characteristics by consuming less power of 2.5 µW. The Wilson current mirror method has benefited the amplifier to enhance the gain and compensation capacitor with series resistor realized by MOSFET device is used in designing 1V powered buffer biased BD FC-OTA for biomedical applications. The layout of a proposed bulk-driven folded cascode amplifier is designed using Cadence Virtuoso has a dimensions of 17.255× 35.5μm.